2020
DOI: 10.24297/jam.v18i.8345
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Computational Fluid Dynamics to Optimize Municipal Sewage Networks; A Case of Tororo Municipality, Eastern Uganda.

Abstract: Two-phase pipe flow is a common occurrence in many industrial applications such as sewage, water, oil, and gas transportation. Accurate prediction of liquid velocity, holdup and pressure drop is of vast importance to ensure effective design and operation of fluid transport systems. This paper aimed at the simulation of a two-phase flow of air and sewage (water) using an open source software OpenFOAM. Numerical Simulations have been performed using varying dimensions of pipes as well as their inclinations. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Hence, its application and simulation use cannot be overemphasised especially in the drying processes. The use of CFD in numerical analysis has shown good results in solving problems of fluid flow with heat and mass transfer, [10] and this has attracted many researchers due to its industrial, environmental, and scientific applications, [11], [12], [13], [14], [15], [16], [17], [18]. [19], analyzed the process of using CFD modeling with the developed threedimensional FBD model while, [20], studied a bubbling flow in a 2D pulsed fluidized bed dryer using the Eulerian approach, and their results showed that pressure changes inside the bed, was due to the formation of air bubbles at minimal frequency pulsating inlet flow causing intermittent fluidized state.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its application and simulation use cannot be overemphasised especially in the drying processes. The use of CFD in numerical analysis has shown good results in solving problems of fluid flow with heat and mass transfer, [10] and this has attracted many researchers due to its industrial, environmental, and scientific applications, [11], [12], [13], [14], [15], [16], [17], [18]. [19], analyzed the process of using CFD modeling with the developed threedimensional FBD model while, [20], studied a bubbling flow in a 2D pulsed fluidized bed dryer using the Eulerian approach, and their results showed that pressure changes inside the bed, was due to the formation of air bubbles at minimal frequency pulsating inlet flow causing intermittent fluidized state.…”
Section: Introductionmentioning
confidence: 99%
“…The pipeline system is one of the most commonly used methods of fluid transportation all over the world. Research on urban sewer pipelines focuses on hydraulics such as pipe slopes and flow rate so that sewage and faecal sludge are to be delivered efficiently (Semwogerere et al, 2020). The flows at the proximity of these structures are typically highly turbulent and often characterized by changes between the open channel and pressurized conditions.…”
Section: Introductionmentioning
confidence: 99%